Dynamics of sperm transport and histological structure of the female reproductive system in Octopus vulgaris (Cephalopoda: Octopodidae) - Hyeon Jin Kim; Jung Jun Park; Chang-Moon Lee; Jung Sick Lee (PLoS ONE, 2026)
In this study, we aimed to provide a detailed microanatomical description of the female reproductive system of Octopus vulgaris , an internally fertilized cephalopod, and to identify its functional characteristics. The female reproductive system of O. vulgaris consists of the ovary, common oviduct, proximal oviduct, oviducal gland, and distal oviduct, and histologically, the structure is similar to that reported in other octopods. The presence of spermatozoa and spermatophore remnants in the distal oviduct suggests that spermatophoric reaction may occur in this region. The released sperm then migrate to the spermathecae of the oviducal gland, where they are anchored to the epithelial layer via a helical acrosome and stored long-term with the support of secretory cells. During the spent and degenerative stages, sperm detach from the epithelial layer of the spermathecae in the oviducal gland and are released into the central cavity of the oviducal gland, where fertilization is presumed to occur. The fertilized eggs are then coated with secretory substances from the central and peripheral glands and subsequently pass through the acidic distal oviduct before being released. These findings demonstrate that the female reproductive system of O. vulgaris exhibits structural differentiation necessary for spermatophoric reaction, sperm storage, and fertilization. This study provides fundamental insights into the reproductive process of internally fertilized cephalopods and serves as a valuable reference for future research on cephalopod reproductive physiology.